Koncepcja „nieuświadomionego Boga” — rozważania po Holocauście Victora Frankla - Nieć, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article presents an idea of „the unconscious God” of V. Frankl 1905–1997, a psychoanalyst and afounder of so called „third Vienesse school”. Frankl, a prisoner of Auschwitz no. 119104 and Dachau, analyzes a modern World as a doctor psychiatrist and a philosopher. The author shows how experience of concentration camps 1942–1945 influences his moral philosophy. In his, avictim of the Holocaust, opinion, modern society is endlessly in crisis, which appears to begin in modern Europe. Frankl, in a book „The Unconscious God”, gives an option to modern human and also discusses on the one hand a pessimistic vision of „death of God” in Auschwitz M. Buber, H. Jonas, and on the other optimistic vision of neopsychoanalysis E. Fromm.
Keywords: psychoanaliza; nowoczesne społeczeństwo; Auschwitz; filozofia moralna; kościół katolicki; kondycja społeczna